Clima educativo familiar y su relación con la madurez para el aprendizaje de la lectoescritura en niños/as de 5 años en la I.E N°205 Rosario del Águila Rojas - Peña Garcia, Angelica (2013)
The aim of this research was to establish the relationship between climate family educational and maturity for literacy learning in child 1 as of 5 years of school No. 205 "Rosario Eagle Red"- industry Capironal City Rioja, in 2011. The research was conducted with a sample of 30 children 1 as, is descriptiva, correlational level, the instruments used were the questionnaire of family educational climate and Filho ABC Test to assess learning of literacy. The collected data were processed using the frequency distribution and the Pearson correlation coefficient; hypothesis testing was performed considering the 1% significance level. After analyzing the results it is concluded that significant relationship between climate family education and maturity for literacy learning in children 1 as of school tnitial No. 205 "Rosario Eagle Red" sector Capironal city Rioja . in 2011, with a correlation coefficient of 0.86 to 1% level of significance. In most children 1 as (43.33%) your home has aclimate characterized by bad education, likewise, maturity for literacy learning of most children 1 as (60%) is lower level.